Post-occupancy evaluation of the neo-vernacular "courtyard" in contemporary mass housing. Case study: 124 duplex dwellings by the El Miniawy brothers in Biskra (Algeria) - Meliouh, Fouzia; Sekhri, Adel; Tabet Aoul, Kheira Anissa; Hamel, Khalissa (Technium Social Sciences Journal, 2023)
In the vernacular housing, the courtyard is the main structural space, whether by its location, function, or symbolism. The experience of El Miniawy brothers in their project "124 logements CNEP" at Biskra with its typology was promoted as "the alternative" to the conventional and traditional "courtyard house." It was reformulated as a new multi-housing typology. Their approach is based on the conversion of the traditional house’s organisation around the "courtyard" from a horizontal to a vertical one in the contemporary house. This vision is argued by its designers as being inspired by local life way, to reformulate the "courtyard" space in a contemporary living environment. The present paper is an investigation that aims to evaluate this experimental project and see if it succeeded in convincing its residents as an alternative to both conventional contemporary housing and vernacular one. The study is based on two approaches. A literature review of the architects’ arguments to promote the typology they suggest and a post-occupancy evaluation (POE) of their project, applied in two steps. The first is observation through architectural surveys and photography, and the second is a questionnaire distributed to project residents. As a main result of the confrontation of the environmental intentions of the architects, with the results of the post-occupancy evaluation, the study showed that the conceptual approach adopted for these "courtyard houses" did not give the results expected by its designers. This was manifested through several parameters studied, but mainly by the declared uses, which are very restricted compared to those provided by the courtyard in the vernacular habitation.